2003
DOI: 10.1038/sj.onc.1207037
|View full text |Cite
|
Sign up to set email alerts
|

Induced genomic instability in irradiated germ cells and in the offspring; reconciling discrepancies among the human and animal studies

Abstract: Many studies confirmed that radiation induces genomic instability in whole-body systems. However, the results of the studies are not always consistent with each other. Attempts are made in the present review to resolve the discrepancies. Many of the studies in human and experimental animals utilize the length change mutation of minisatellite sequences as a marker of genomic instability. Minisatellite sequences frequently change their length, and the data obtained by conventional Southern blotting give rather q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…These and other data suggest that minisatellite mutation rates may be useful biomarkers of germline genetic effects caused by environmental mutagens such as IR (Yauk, 2004;Bouffler et al, 2006). As minisatellites do not appear to be the direct target of mutagen-induced DNA damage (Dubrova et al, 1996(Dubrova et al, , 1997, it is thought that they may act as a marker for general genome sensitivity or instability (Niwa, 2003).…”
mentioning
confidence: 95%
“…These and other data suggest that minisatellite mutation rates may be useful biomarkers of germline genetic effects caused by environmental mutagens such as IR (Yauk, 2004;Bouffler et al, 2006). As minisatellites do not appear to be the direct target of mutagen-induced DNA damage (Dubrova et al, 1996(Dubrova et al, , 1997, it is thought that they may act as a marker for general genome sensitivity or instability (Niwa, 2003).…”
mentioning
confidence: 95%
“…Other studies focused on heritable alterations in cancer incidence and teratogenesis following the parental preconception irradiation [Mohr et al, 1999;Pils et al, 1999;Nomura, 2003;Nomura et al, 2004;Dasenbrock et al, 2005]. In addition to this classic evidence for transmitted effects, it is now apparent that risks to the progeny of irradiated parents also include transgeneration genomic instability [Carls and Schiestl, 1999;Mohr et al, 1999;Barber et al, 2002Shiraishi et al, 2002;Dubrova, 2003a,b;Morgan, 2003b;Niwa, 2003;Nomura, 2003;Nomura et al, 2004;Slovinska et al, 2004;Dasenbrock et al, 2005;Tawn, 2005;Singer et al, 2006].…”
Section: Transgeneration Radiation-induced Effectsmentioning
confidence: 99%
“…Additionally, in some studies the extent to which somatic mutations (as revealed by mosaicism) are included in the scores is not clear. Niwa (69) points out that the discrepancies may be due to different end points being measured in the two laboratories: embryonic instability after latestage exposures and direct germline mutation after pre-meiotic exposures.…”
Section: The Controversy Over the Mutability Of Different Mouse Germ mentioning
confidence: 99%
“…A number of authors have suggested that epigenetic changes may be involved in transgenerational ESTR mutation (40,42,69). Epigenetic modifications will alter DNA function without changing the underlying nucleotide sequence; one example is that of genes that can be silenced through the methylation of CpG dinucleotides in their regulatory sequences.…”
Section: Enhanced Mutation At Estrsmentioning
confidence: 99%